Pemberdayaan Santri Pondok Al-Fatih Jombang: Pengolahan Limbah Organik dan Pengembangan Biomist Bernilai Ekonomis-Ekologis - Rochmah, Luthfi Maulida; Muzakky, Mohamad Irvan; Aruna, Alby; Prasetyo, Abdur Rahman (Sahabat Akademia Group, 2024)
Pondok Al-Fatih Tambakberas in Jombang faces a pressing issue with organic waste, which has yet to be effectively processed. To address this, an initiative aimed at optimizing organic waste management was launched through the empowerment of students. This was achieved by conducting training sessions on converting organic waste into high-quality biomist, which holds substantial economic and ecological potential. The training was part of a community service program and was conducted using a qualitative method based on the Logical Framework Approach (LFA), chosen for its structured process and focus on achieving clear objectives. The stages involved: (1) problem identification, (2) stakeholder analysis, (3) goal setting, (4) development of an activity plan, (5) resource identification, (6) training implementation, and (7) monitoring and evaluation. The outcomes indicate that the program was highly effective, with an 87% increase in community awareness, an 83% improvement in waste processing efficiency, and the establishment of biomist quality standards aiming to meet industrial benchmarks. Additionally, the biomist produced was found to hold both economic and ecological value.